Pengaruh Metode Problem Posing pada Kemampuan Berpikir Kritis Peserta Didik Kelas X IPS pada Pembelajaran Sejarah di SMA Muhammadiyah 1 Pontianak - Pratiwi, Nuri Yusticia; Chalimi, Ika Rahmatika; Ulfah, Maria (CV. Rayyan Dwi Bharata, 2025)
This research aims to determine the effect of problem posing method on critical thinking of X social studies class students at SMA Muhammadiyah 1 Pontianak. In this research new experimental quantitative research methods. The source of data taken was class X IPS 3 as the experimental class and class X IPS 4 as the control class. The used data gathering procedures include observation, test questions, and documentation. The data analysis procedures used include validity testing, reliability testing, normality testing, homogeneity testing, hypothesis testing, and effect size testing. The results showing that: (1). For the experimental group, the average results of the pre- and post-tests were 57.60 and 79.40, respectively. For the control group, the average results of the pre- and post-tests were 64.60 and 66.90, respectively. We may reject the null hypothesis since the t-test result of 8.36 is greater than the significance level of 2.00. The impact size calculation also came out at 0.45, which is considered medium. Class X social studies students at SMA Muhammadiyah 1 Pontianak's critical thinking abilities are impacted by the problem posing learning approach, according to the t-test results and effect size analysis.